"The Poor Mystery of My body": The Sanctity of the Human in Illness and Death. Issue 4 (October 2018) - Brennan, Frank
Respect for the human body is a fundamental principle of health care. This article examines a selection of the work of three Polish poets who lived through the agonies of World War II. The author reflects on the lessons that can be drawn from their work for clinical care, including Palliative Care, the dignity of the human person and the nature of suffering.